FORMULATION ANTIAGING CREAM MELASTOMA MALABATCHRICUM EXTRACT WITH POLYOXYETHYLENE MONOSTEARATE AND STEARIC ACID - Mukti, Yusuf Anggoro; Gunawan Pamudji Widodo; Teuku Nanda Saifullah Sulaiman (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Karamunting fruit (Melastoma malabathricum L.) contains flavonoids, triterpenoids and tannins. The purpose of this study was to make anti-aging cream preparations using caramunting fruit extract with a combination of PEG 40 stearic acid and stearic acid to obtain optimum physical quality. Extract with 96% ethanol filter in the form of extracts used for cream preparations using a base of PEG 40 stearic and stearic acid, so that 8 formulas were obtained, then optimized based on the physical quality parameters of viscosity, spreadability, adhesion and pH, then optimization of the formula to determine the formula optimum using the Simplex Lattice Design method. The conclusion obtained based on this research is the optimum combination of PEG 40 stearic and stearic acid in the cream of caramunting fruit extract using the Simplex Lattice Design method, namely PEG 40 Stearate 4.76% and stearic acid 15.74%. The physical quality stability did not change during one month of storage and the cream did not cause irritation. Formula I had a better and almost equal effect on the collagen test while formula V had a better effect on the elasticity test and the moisture test.